2006
DOI: 10.1081/lft-200053856
|View full text |Cite
|
Sign up to set email alerts
|

Downhole Separation of Petroleum Fluids

Abstract: Oil-water separation is one of the oldest practices in the purification of water or oil. Environmentally concerned organizations pay more attention to the purification of water, while oil companies concentrate on the purification of oil. Water management is particularly an important issue in the production of hydrocarbons, because volumes of water steadily increase as a field ages. In fact, increasing costs of water handling such as separation, disposal, treatment, maintenance, and environmental risks make the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Presumably, the retentate could include fines and flocculated molecules with a length scale greater than the nominal pore size of the membrane. Jamaluddin and co-workers have commented on the filtration of live crudes through similarly hydrophobic membranes and observed that there was a significant amount of retentate containing asphaltenes that did not pass through a 0.22 μm pore size membrane. Others have studied similar phenomena for downhole application . We conclude that the crude oils pass through the membrane unimpeded as long as there is not a significant amount of asphaltene flocculation due to a reduction in pressure or addition of alkane.…”
Section: Resultsmentioning
confidence: 68%
“…Presumably, the retentate could include fines and flocculated molecules with a length scale greater than the nominal pore size of the membrane. Jamaluddin and co-workers have commented on the filtration of live crudes through similarly hydrophobic membranes and observed that there was a significant amount of retentate containing asphaltenes that did not pass through a 0.22 μm pore size membrane. Others have studied similar phenomena for downhole application . We conclude that the crude oils pass through the membrane unimpeded as long as there is not a significant amount of asphaltene flocculation due to a reduction in pressure or addition of alkane.…”
Section: Resultsmentioning
confidence: 68%